2022
DOI: 10.1039/d1cc07013d
|View full text |Cite
|
Sign up to set email alerts
|

Visible-light driven water oxidation and oxygen production at soft interfaces

Abstract: The visible light driven water oxidation reaction (WOR) by the organic electron acceptor 2,3,5,6-Tetrafluoro-7,7,8,8-tetracyano-quinodimethane (TCNQF4) was studied at the water|butyronitrile interface. The WOR was performed at neutral pH, and without...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
(22 reference statements)
0
4
0
Order By: Relevance
“…Moreover, direct contact of photosensitizer with the electrode allows for its recycling. Importantly, it was demonstrated that application of 10 nm tetrafluorinated 7,7,8,8‐tetracyano‐quinodimethane aggregates having strong electron affinity as sensitizer simplifies the system: OER occurs without any metal, metal oxide or molecular catalyst [82] …”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, direct contact of photosensitizer with the electrode allows for its recycling. Importantly, it was demonstrated that application of 10 nm tetrafluorinated 7,7,8,8‐tetracyano‐quinodimethane aggregates having strong electron affinity as sensitizer simplifies the system: OER occurs without any metal, metal oxide or molecular catalyst [82] …”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
“…So far few studies of OER at polarized liquid|liquid interface were reported [9,13,78–82] . All studied systems are based on nanoparticulate film assembled at liquid|liquid interface.…”
Section: Oxygen Evolution Reaction (Oer)mentioning
confidence: 99%
“…Electrochemistry at the interface between two immiscible electrolyte solutions (ITIES) found different applications over the years that include oxygen reduction, [1–3] metal ion extraction, [4,5] water oxidation, [6] metal deposition, [7–9] electrocatalysis [10–13] and analytical assays for quantification of a vast number of analytes [14–23] . The success of this technology arises from the fundamental improvements introduced in the ITIES systems over the last decades, such as the four electrode potentiostats [24] for better potential control and reproducible measurements, the reduction of the interface size [25–33] from macrointerfaces to microinterfaces to improve the sensitivity and the gelation of the organic phase [34–36] that enhanced the stability the liquid‐liquid systems.…”
Section: Introductionmentioning
confidence: 99%
“…TCNQ and its derivatives have been widely used in other practical applications; for example in electronic recording, [1f,g] data and iodine storage, [1h,j,3] sensing, [4] antibacterial fabrics [5] and superhydrophobic surfaces [6] . Their use as catalysts [1d,k,7] to speed up the [Fe(CN)6]​3- /normalS2normalO32- reaction, [1d,k] remediate environmental pollutants [7b] (e. g. reduce high toxicity chromium into relatively nontoxic trivalent chromium species), and for water oxidation also has been of interest [7c,8] . Furthermore, the absorption properties of TCNQ and its derivatives across the UV‐vis‐IR region have led to them being explored as broad‐spectrum photoactive catalysts [9] .…”
Section: Introductionmentioning
confidence: 99%